The effect of tectonic plate motion on georeferenced long-term global datasets - Mocnik, Franz-Benjamin; Westerholt, René (International journal of applied earth observation and geoinformation, 2021)
Tectonic plate motion affects coordinates resulting from GPS measurements and the referencing of aerial and satellite imagery. It therefore impacts the long-term use of global coordinate systems. Over time, the tectonic plates move relative to each other and coordinates become outdated. Most geographic datasets including OpenStreetMap are no exception, as these are affected in terms of a growing location-coordinate mismatch. Current research is aware of this issue but solution strategies have not been fully explored yet. In this manuscript, we discuss how regular systematic updates of coordinate values can be used to address this issue. We explore the recommended frequency to perform such updates for guaranteeing a minimal loss of accuracy after long periods of time. It is further determined how rounding errors impair such systematic updates and in which ways singular and irregular manual updates impede systematic solution strategies. The solution strategies proposed lead to minimal overall errors and thus guarantee to retain high positional accuracy of coordinate pairs within global datasets, even after years of existence.